LILRA5+ macrophages drive early oxidative stress surge in sepsis: a single-cell transcriptomic landscape with therapeutic implications - Xu, Peng; Li, Haoze; Tao, Zuo; Zhang, Zixuan; Wang, Xiaohuan; Zhang, Cheng (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundIn sepsis, oxidative stress (OS) triggers essential adaptive responses and emerging OS-related biomarkers show potential for enhancing sepsis diagnosis and therapy.MethodologyIn this study, we used single-cell datasets and the OS gene set to identify immune cell types with the highest oxidative activity across different sepsis states. Differential expression genes (DEG) between “high state” cells and “low state” cells were screened. High-dimensional weighted gene co-expression network analysis (hdWGCNA), combined with multiple machine learning methods, was used for the selection of hub genes. Expressions of hub genes were then validated. Cell–cell communication and transcription factor analysis were performed later. Real-time quantitative reverse transcription (qRT-PCR) and Western blotting validated expression of LILRA5 in both the cecal ligation and puncture (CLP) model and the lipopolysaccharide-induced sepsis model. Reactive oxygen species (ROS) levels were also detected in THP-1 cells after silencing LILRA5.ResultsIn the early stages of sepsis, oxidative activity reaches its peak, with macrophages displaying the highest OS among all cell types. Through the application of the “Quartile method”, all cells were clustered into three states based on OS activity (low, medium, and high). LILRA5, MGST1, PLBD1, and S100A9 were selected as hub genes and significantly upregulated in sepsis. LILRA5 was predominantly expressed in macrophages and was highly expressed in the early stage of macrophage. Specifically, LILRA5+ macrophages exhibit the strongest OS. LILRA5 showed a higher expression in both mouse sepsis models and the THP-1 cell after lipopolysaccharide stimulation. Silencing LILRA5 resulted in a significant reduction of ROS in THP-1 cells.ConclusionIn conclusion, our study has mapped the landscape of OS dynamics in sepsis and found that LILRA5+ macrophages in the early stage of sepsis exhibit the highest OS. LILRA5 emerges as a promising gene for modulating macrophage-mediated OS in sepsis.